Designing Android based Mobile Application for Earth Layer Learning at Junior High School - Shofiyah, Noly; Untari, Rahmania Sri; Saputra, Yofanka Eko Ardian (Universitas Negeri Malang, 2022)
The complexity of science topics makes it difficult for students to understand all science concepts correctly. Mobile devices can help students to be more focused and efficient in learning. The study aimed to develop the android - based mobile application about the earth layer and include its natural disaster concept. The development model used was the 4D Model. This research produces a product in the form of Earth Panel Cellular Application. The expert validation average score of 3.38, which is in the excellent category, shows that the earth layer application is suitable for usage. The application's effectiveness can be quite effective in enhancing students’ cognitive learning outcomes based on the gained sig. The significance of application is said to be quite effective in improving cognitive learning outcomes with a value of 0.000 less than 0.05